THE ROLE OF KARNATAKA IN THE BHAKTI MOVEMENT (International Journal of Food and Nutritional Sciences, 2022)
The Bhakti Movement, which flourished between the 7th and 17th centuries, had a profound impact on Indian society, particularly in the southern regions. Karnataka, in particular, played a crucial role in the development and spread of the Bhakti Movement, serving as a birthplace for several influential saints and poets who emphasized devotion to God as the path to liberation. This paper examines the role of Karnataka in the Bhakti Movement, focusing on key figures such as Basava, Allama Prabhu, and the Vachana poets. The study explores the philosophical underpinnings of the movement, its influence on social reform, and its contribution to Kannada literature. Furthermore, it draws parallels between the values of the Bhakti Movement and their relevance to modern-day issues such as communal harmony, personal devotion, and spiritual upliftment.